Exploring the Role of Practitioner Confidence in Prevention and Early Intervention in Child Welfare: A Case Study of Irish Youth Workers in Meitheal. Issue 4 (3rd July 2020) - Healy, Maria; Rodriguez, Leonor
ABSTRACT: This study analyses the role of youth workers' confidence in Meitheal: an Irish model of prevention and early intervention in child welfare. This study had an exploratory mixed methods design. Semi-structured interviews were carried out with youth workers to analyse their knowledge of prevention, early intervention, Meitheal and partnerships in child welfare. These were analysed using inductive thematic analysis. Additionally, youth workers completed a questionnaire to explore the levels of confidence in their role. Due to the small sample only descriptive and non-parametric statistics were used to analyse the data obtained. Youth workers see support and advocacy of young people as their primary role in Meitheal, despite this, participants described explaining what they do with other child welfare agencies as a challenge which was understood as a possible insecurity on the part of youth workers, alongside a presumption that their role and profession is not understood. Overall, this study found the need for youth workers to be more confident when engaging in Meitheal to facilitate their role and ensure that young people and their families are appropriately supported by the discipline of Youth Work specifically but also as part of the overall Meitheal model.